Cyber Rights and Digital Security: Protecting Human Rights in The Online World - M. Rusdi; Astriyani A. Papuangan; Abdi Wael; Syamsuddin Syamsuddin; Ardi Marinda; Rini Rukua (PT. Global Research Collaboration, 2025)
The rapid expansion of digital technology has created new opportunities for social participation while simultaneously introducing challenges to human-rights protection in cyberspace. Communities in rural Indonesia, particularly in the Maluku region, often face limited awareness of digital rights and online security, making them vulnerable to cyber threats and misinformation. This community service program titled “Cyber Rights and Digital Security: Protecting Human Rights in the Online World” was conducted in Tulehu Village, Central Maluku, to enhance citizens’ understanding of digital rights, cybersecurity, and ethical online behavior. Using participatory methods Focus Group Discussions (FGDs) and structured presentations the project engaged 80 participants representing youth, women, educators, and community leaders. The activities emphasized awareness of data privacy, digital ethics, and safe internet practices while linking them to the broader concept of human rights. Results showed a significant increase in participants’ knowledge and behavioral transformation toward responsible digital citizenship. The formation of the Digital Awareness Forum (DAF) ensured program sustainability by enabling continuous education and collaboration with local governance. The outcomes demonstrate that contextualized, rights-based digital-literacy programs can empower rural communities to navigate online spaces safely and ethically. This initiative offers a replicable model for integrating human-rights education with digital transformation, reinforcing that protecting human dignity in the digital era requires awareness, empowerment, and cultural adaptation.